2023
DOI: 10.3390/ijerph20032324
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone-Based Nutrition Education Targeting Pregnant and Nursing Mothers in Sri Lanka

Abstract: Introduction: A woman’s nutrition during pregnancy and nursing affects the mother and the growing child. Similarly, the first two years of a child’s life are critical to their growth and development and are facilitated by optimum nutrition. Women’s nutrition-related knowledge, attitudes, and practices influence household food and nutrition security. Mobile health (mHealth) is a potentially effective health intervention in pandemic situations when physical gatherings are restricted. Objectives: To examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Although the observed difference was higher in our study, it is important to note that the MDD-W percentage obtained in our study was lower than that reported in previous studies conducted in the country (67.8% vs. 96.9%) (11). This may be mainly due to differences in the sociodemographic characteristics of our population.…”
Section: Socio-demographic Characteristics Of the Participantscontrasting
confidence: 94%
See 2 more Smart Citations
“…Although the observed difference was higher in our study, it is important to note that the MDD-W percentage obtained in our study was lower than that reported in previous studies conducted in the country (67.8% vs. 96.9%) (11). This may be mainly due to differences in the sociodemographic characteristics of our population.…”
Section: Socio-demographic Characteristics Of the Participantscontrasting
confidence: 94%
“…We developed messages in the Sinhala and Tamil languages. The description of the message development and sample content were similar to those in our previous study (11). The messages developed were tested on ten people who were not selected for this study.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of research with interventions using social media are external factors that researchers cannot predict, for example participants could be influenced by information from outside such as from mass media.This way, interventions using social media combined with other media may be more effective (Wyst et al, 2019). Overall, The implementation of education using social media must be supported by primary health service system from local to national level so that it can be utilized more optimally (Peiris et al, 2023). Researchers think that providing education through social media is an effective way to be implemented in the era of technological development nowadays.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting Pregnant and Nursing Mohers in Sri Lanka (Peiris et al, 2023) Before and after withinsubject design 720 pregnant and nursing mothers…”
Section: Mobile Phone-based Nutrition Educationmentioning
confidence: 99%